2016
DOI: 10.1016/j.tecto.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effects of oblique extension on continental rift interaction from 3D analogue and numerical models

Abstract: Continental rifts often develop from linkage of distinct rift segments under varying degrees of extension obliquity. These rift segments arise from rift initiation at non-aligned crustal heterogeneities and need to interact to develop a full-scale rift system. Here, we test the effects of 1) oblique extension and 2) initial heterogeneity (seed) offset on continental rift interaction with the use of an improved analogue model setup. X-Ray computer tomography (CT) techniques are used to analyse the 3D models thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
120
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 61 publications
(65 reference statements)
17
120
0
3
Order By: Relevance
“…Data from numerical and analog studies indicate the influence of various parameters on rift interaction, e.g., the presence and geometry of structural heterogeneities, such as fault and shear zones, detachment layers, and magma intrusions that determine what structures develop (Elmohandes, 1981;Naylor et al, 1994;Acocella et al, 1999Acocella et al, , 2005Basile and Brun, 1999;Le Calvez and Vendeville, 2002;McClay et al, 2002;Tentler and Acocella, 2010;Paul and Mitra, 2013;Brune, 2014;Zwaan et al, 2016). Key factors affecting the large-scale evolution of rift interaction structures are the rift offset and the degree of brittle-ductile coupling in the system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from numerical and analog studies indicate the influence of various parameters on rift interaction, e.g., the presence and geometry of structural heterogeneities, such as fault and shear zones, detachment layers, and magma intrusions that determine what structures develop (Elmohandes, 1981;Naylor et al, 1994;Acocella et al, 1999Acocella et al, , 2005Basile and Brun, 1999;Le Calvez and Vendeville, 2002;McClay et al, 2002;Tentler and Acocella, 2010;Paul and Mitra, 2013;Brune, 2014;Zwaan et al, 2016). Key factors affecting the large-scale evolution of rift interaction structures are the rift offset and the degree of brittle-ductile coupling in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Key factors affecting the large-scale evolution of rift interaction structures are the rift offset and the degree of brittle-ductile coupling in the system. Larger offsets between rift segments cause TZs to be narrower (Acocella et al, 1999;Dauteuil et al, 2002) or even prevent TZs from developing (Le Calvez and Vendeville, 2002;Allken et al, 2011Allken et al, , 2012Zwaan et al, 2016). However, initial accommodation zones tend to evolve into TZs with increasing deformation ) and higher strain rates increase transfer zone widths (Dauteuil et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, however, where we investigate the frequency of oblique rifting, it appears to be useful to draw a line between orthogonal and oblique extension. In simplified model settings, previous studies suggested that qualitative differences in the rifting style emerge when rift obliquity exceeds 15 to 20° (Clifton et al, 2000;Agostini et al, 10 2009;Brune, 2014;Zwaan et al, 2016). Keeping in mind that the specific value is somewhat arbitrary, we will use 20° as the critical obliquity separating orthogonal from oblique rifts.…”
mentioning
confidence: 99%